Glossary of Astronautics - Swedish Language Council, Institute for Language and Folklore (Institute for Language and Folklore, 2023)
The term collection is made available by ISOF, the Institute for Language and Folklore. It was originally developed at TNC in collaboration with the Swedish Space Research Committee. The translated terms has been produced in collaboration with Adam Dattner, Paris.

The glossary contains 510 terms in Swedish. The terms are also translated to Russian, German and English.

Flerspråkig terminologisamling som rör rymdtermer. Ordlistan har utarbetats av TNC i nära samarbete med Rymdnämnden. Dom översätta termerna har tagits fram i samarbete med Adam Dattner, Paris.

Samlingen innehåller 510 termer på svenska. Termerna är även översatta till ryska, tyska, franska och engelska
Rymdordlista
Keywords: Swedish centre for terminology; Tekniska Nomenklaturcentralen; Multilingualism; Flerspråkighet; glossaries; ordlistor; space; rymd; Languages and Literature; Språk och litteratur